Flutter Application for Dormitory Resident Monitoring (Case Study: Lambung Mangkurat South Kalimantan Student Dormitory) - Abdurrahman Yusuf Wijasena; Muhammad Zakariyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The management of the Lambung Mangkurat South Kalimantan Student Dormitory is responsible for providing reports on their dormitory residents. These reports include personal data and Study Result Cards to confirm that boarders are students. However, currently, the administrators use WhatsApp groups to collect these reports, which causes a backlog and difficulty in data collection. Therefore, a research project was initiated to develop an application that can assist residents and administrators in collecting and managing these reports. The app serves as a monitoring and evaluation tool for the boarders. It can also track their financial, academic, and daily picket activity reports. The research started with a literature study to identify the problems and objectives of the project. The current system procedures were analyzed to identify areas that needed improvement. Based on the research results, an Android-based application was developed and successfully implemented at Lambung Mangkurat South Kalimantan Student Dormitory. This application has features that allow dormitory managers to monitor daily picket activities, academic reports, and cash billing information more efficiently.